THE ACQUISITION OF ENGLISH MULTIPLE INTERROGATIVES BY INDONESIAN SPEAKERS - Kurniawan, Eri (Universitas Pendidikan Indonesia, 2013)
Abstract: This paper investigates the acquisition of English multiple interrogatives suchas Who did what? by advanced learners of English whose first language is Indonesian. Theunderlying functional feature of multiple interrogatives is multiple focus features, whichare not available in Indonesian. Unlike English, there is no equivalent structure of multipleinterrogatives in Indonesian since wh-questions in this language are instantiations of uniquefocus constructions. Acceptability judgment tasks were administered on four wh-pairings: whowhen,who-where, what-when, and what-where. The first task was in the form of questionswith a pair-list answer and single answer, whereas the second was in the form of questionswithin the contexts. Conjoined interrogatives were also added into the tasks in order to observethe L1 transfer. The results clearly demonstrate that overall advanced learners of English weresignificantly different from the English native speakers in their ratings of acceptability ofmultiple interrogatives. However, the statistical data of each wh-phrase pairing demonstratesthat L2 learners performed like native controls in their ratings of most of the pairings. Thesefindings suggest that the present study lends partial support to Full Transfer/Full AccessHypothesis and No Parameter Resetting Hypothesis.